PENCIPTAAN SANGGUL SAKELLYA DENGAN SUMBER IDE BUNGA SAKURA UNTUK PENATAAN RAMBUT FANTASI - Nadyaning Widya Ayu Lukita Hermawan; Mutimmatul Faidah; Octaverina Kecvara Pritasari; Dewi Lutfiati (Jurnal Tata Rias, 2026)
The creation of the Sakellya bun inspired by cherry blossoms discusses the process of producing the work as well as respondents’ assessments of the result in the context of fantasy hair styling. The creation process was carried out through several interconnected stages, namely exploration, design, and realization. The exploration stage was conducted by observing the visual characteristics of cherry blossoms, including the shape of the petals, texture, and color gradation, accompanied by an exploration of the philosophical meaning of cherry blossoms as symbols of beauty, softness, and transience. The results of the exploration were then translated into the design stage by developing two alternative fantasy bun designs that present an interpretation of cherry blossom petal forms. Based on aesthetic and technical considerations, the second design was selected because it has a more dominant visual strength and is more suitable for the character of a fantasy bun. The realization stage was carried out through three trials to obtain a bun shape that is proportional, stable, and in accordance with the concept by applying backcombing, rolling, and layering techniques, as well as using synthetic hair with pink color gradation. The final result shows that the Sakellya bun is able to present the visual appearance of blooming cherry blossom petals with a strong structure while remaining comfortable to wear. The evaluation of the work was conducted through interviews with the academic supervisor, a hairdressing expert, and the model, as well as through questionnaires distributed to 35 students of the Cosmetology Education Study Program. The assessment results show that the work has conceptual suitability, technical accuracy, a strong structure, and comfort in use with an average score of 4.81 in the “Strongly Agree” category.